Ende wider Willen: Schönbergs Moses und Aron : die Tragödie des Monotheismus - Assmann, Jan (Poetica, 2020)
Abstract Schoenberg did not intend his opera Moses and Aron to be a tragedy. The two acts he composed, which end tragically with Moses’ desperate breakdown, were to be followed by a third act, which would have ended with Moses’ resilience, Aron’s death, and a positive message. Schoenberg, however, did not manage to compose the finished text, although he had plenty of time to do so. Even though Schoenberg never wanted to admit this, the opera found its ultimate, unsurpassable ending with the tragic end of the second act.